The importance of human interaction for curriculum and school life satisfaction among Japanese medical graduates: A web-based survey study - Nobuyasu Komasawa; Masanao Yokohira (PLoS ONE, 2025)
Background This study aimed to assess the curriculum and school life of Japanese medical students on the verge of graduation. Methods A web-based questionnaire survey was conducted to gauge the goals of graduating medical students across various themes: Subjective academic achievement in each curriculum, Length of each curriculum, Timing for summative examination preparation, and Satisfaction with total medical school life, accomplishments, extracurricular activities, and friendships. Results With a 67.8% response rate (80/118), the study found that subjective accomplishment in Clinical Clerkship (CC) was significantly lower than in other curriculums (P<0.05 each). Social medicine had significantly lower subjective accomplishment compared to basic medicine (P=0.040). Graduating students reported that the basic medicine curriculum was significantly longer than clinical medicine, CC, and general education (P < 0.05 each). Preparation timing for Pre-CC and Post-CC OSCE was significantly later compared to other summative tests (P < 0.05 each). Total satisfaction with medical school life correlated significantly with school friendships (P < 0.001), while subjective accomplishment and extracurricular activity did not. Conclusion Graduating medical students express lower subjective accomplishment in CC compared to other curriculums, suggesting a need for CC content improvement. Additionally, the study highlights the significant role of school friendships in influencing total medical school life satisfaction.